Community-based prevalence versus hospital-based incidence of genital Human Papillomavirus infection in Central Vietnam - Vu Quoc Huy Nguyen; Viet Quynh Tram Ngo; Minh Tam Le; Hoang Bach Nguyen; Van Bao Thang Phan; Quang Vinh Truong; Ngoc Thanh Cao; Piero Cappuccinelli (Journal of Infection in Developing Countries)
Introduction: This study aims to determine the genital HPV prevalence in reproductive-age women in Thua Thien Hue Province and comparison with HPV incidence in Hue University Hospital, Vietnam.